Volitional questionnaire: Psychometric evaluation of the finnish translation. (17th February 2020) - Fan, Chia-Wei; Keponen, Riitta; Piikki, Sanna; Popova, Evguenia; Taylor, Renee
Abstract: Background: Supporting clients' motivation to engage in occupations is essential to occupational therapy practice. The Volitional Questionnaire Finnish version (VQ-FI) can be used to evaluate volitional behaviors of clients with limited ability to communicate. Objective: The many-facet Rasch model was used to evaluate the reliability and validity of the VQ-FI using the FACETS and WINSTEPS software. Methods and materials: Forty-two therapists received an in-person training on the VQ-FI and completed 226 independent ratings of clients. The VQ-FI was evaluated in its rating scale functioning, unidimensionality, person validity, rater severity, item targeting, and item/person separation. Results: The four-point rating scale demonstrated adequate functioning; the 'passive' rating category was rarely adopted. The VQ-FI showed unidimensionality, with all 14 items fitting the Rasch model. No evidence for ceiling or floor effects, and the assessment demonstrated appropriate item and person separation. The VQ-FI reliably separated participants to three levels of ability. Conclusions: The study provides preliminary evidence for the reliability and validity of the VQ-FI. Significance: The VQ-FI is an observational measure that can be used to evaluate clients' volitional behaviors. The VQ-FI offers practitioners and researchers a valid approach to evaluate volition that is theoretically grounded in the Model of Human Occupation.